2013
DOI: 10.5430/wje.v3n5p45
|View full text |Cite
|
Sign up to set email alerts
|

School Teachers’ Knowledge about Autism in Saudi Arabia

Abstract: The purpose of this study was to find out what school teachers know about Autism. In addition, this study attempted to find out if there any significant differences in school teachers' knowledge about Autism depending on teachers' (gender, position, education level, teaching experience, and contact with students with Autism) variables. A total of 391 general and special education teachers from various segregated and inclusive schools within the Jeddah in Saudi Arabia completed study instrument (Autism knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 27 publications
11
49
3
6
Order By: Relevance
“…In this cross-sectional study we tried to figure out the level of knowledge of school teachers about Autism which was identified as 48.7%, which Implies weak level of knowledge among them. In contrast to a second research done in Saudi Arabia in Jeddah which was 58% (15). Another researcher from Saudi Arabia tried to explore the burden of ASD in the Gulf area, by studying all published articles in Pubmed and Science direct to review the current state of knowledge of epidemiology on autism in the GCC, and make recommendations for future research (3).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In this cross-sectional study we tried to figure out the level of knowledge of school teachers about Autism which was identified as 48.7%, which Implies weak level of knowledge among them. In contrast to a second research done in Saudi Arabia in Jeddah which was 58% (15). Another researcher from Saudi Arabia tried to explore the burden of ASD in the Gulf area, by studying all published articles in Pubmed and Science direct to review the current state of knowledge of epidemiology on autism in the GCC, and make recommendations for future research (3).…”
Section: Discussioncontrasting
confidence: 66%
“…Our study identified a statistical significant difference between public schools, and private school teachers’ knowledge; However, in contrast to all other researches the mean of public school was more than private school teachers, which could be attributed to unequal sample size (222/26). School type definitely affect level of knowledge, this result was confirmed by (15), where they emphasis on the fact that special education private school teachers had elevated level of knowledge more than public school teachers. Other researchers agreed with this result that public-school teachers were in more need for training programs regarding dealing with autism children (19).…”
Section: Discussionmentioning
confidence: 59%
“…Internal consistency scores were the most commonly reported type of reliability (Bakare et al, 2008; Campbell and Barger, 2011; Campbell et al, 1996; Furnham and Buck, 2003; Garg et al, 2014; Gillespie-Lynch et al, 2015; Haimour and Obaidat, 2013; Johnson and Van Hecke, 2015; Kuhn and Carter, 2006; Mavropoulou and Sideridis, 2014; Obeid et al, 2015; Ross and Cuskelly, 2006; Segall and Campbell, 2012, 2014; Talib and Paulson, 2015), with some studies also reporting test–retest reliability (Al-Sharbati et al, 2015; Bakare et al, 2008; Vijayarani, 2014) or inter-rater reliability (Al-Sharbati et al, 2015). Occasionally, studies reported measure construct validity (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing legislative demands placing an emphasis on teacher qualities raise questions about teachers who work with students with Autism Spectrum Disorder. As a result, it has become increasingly necessary to ensure school teachers are adequately prepared and possess requisite knowledge and skills (Haimour & Obaidat, 2013).…”
Section: International Education Studiesmentioning
confidence: 99%
“…To provide better life opportunities for these individuals, it was necessary to train teachers and develop their skills. Teachers are considered the better persons who can diagnose challenges and identify appropriate strategies to develop their skills (Haimour & Obaidat, 2013).…”
Section: Introductionmentioning
confidence: 99%